2019
DOI: 10.1085/jgp.201912390
|View full text |Cite
|
Sign up to set email alerts
|

Effects of FGF14 and NaVβ4 deletion on transient and resurgent Na current in cerebellar Purkinje neurons

Abstract: Voltage-gated Na channels of Purkinje cells are specialized to maintain high availability during high-frequency repetitive firing. They enter fast-inactivated states relatively slowly and undergo a voltage-dependent open-channel block by an intracellular protein (or proteins) that prevents stable fast inactivation and generates resurgent Na current. These properties depend on the pore-forming α subunits, as well as modulatory subunits within the Na channel complex. The identity of the factors responsible for o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(51 citation statements)
references
References 84 publications
(208 reference statements)
3
47
0
Order By: Relevance
“…As such, we expect intact FHF binding to the F1759A mutant. Na V channels in Purkinje neurons exhibit a resurgent current that results from open-state block by intracellular endogenous proteins, including FGF14 and the cytosolic domain of the Na V β4 subunit ( 52 ). Interestingly, such endogenous open-channel blocking proteins antagonize lidocaine action, suggesting that the 2 sites may be coupled ( 53 ).…”
Section: Discussionmentioning
confidence: 99%
“…As such, we expect intact FHF binding to the F1759A mutant. Na V channels in Purkinje neurons exhibit a resurgent current that results from open-state block by intracellular endogenous proteins, including FGF14 and the cytosolic domain of the Na V β4 subunit ( 52 ). Interestingly, such endogenous open-channel blocking proteins antagonize lidocaine action, suggesting that the 2 sites may be coupled ( 53 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that overexpression of FGF14-1b in hippocampal neurons potentiates transient Na + currents (Laezza et al, 2007), while genetic deletion of FGF14 leads to reduced Na + currents and firing in several neuron subtypes including MSNs in the NAc (Ali et al, 2018;Goldfarb et al, 2007;White et al, 2019). These phenotypes have been attributed to a role of FGF14 in preserving the pool of active channels, in part by minimizing inactivation and increasing channel availability (White et al, 2019). However, if FLPK acts as an inhibitor of the FGF14:Nav1.6 complex, as suggested by our LCA studies, the effect of the tetrapeptide on persistent Na + currents would be hard to reconcile.…”
Section: Role Of Flpk In Regulating Na + Currents and Excitability In Msnsmentioning
confidence: 99%
“…accessory protein, excitability, inactivation, sodium channels 2020; White et al, 2019). These new studies identify the FLPK tetrapeptide as a useful tool to probe Nav1.6 channel function and a scaffold for future drug development towards treatment of a wide range of channelopathies associated with Nav channels (Alshammari et al, 2016;Chahine et al, 2008;Di Re et al, 2017;Eijkelkamp et al, 2012;Hsu et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kv3.3 is co-expressed in Purkinje cells with the Na v 1.6 voltage-gated Na + channel ( Raman et al, 1997 ; Khaliq et al, 2003 ; Martina et al, 2003 ; Akemann and Knöpfel, 2006 ). During an action potential, Na v 1.6 is subject to open channel block conferred by an auxiliary subunit thought to be Na v β4 or FGF14 ( Grieco et al, 2005 ; White et al, 2019 ). Rapid repolarization mediated by Kv3.3 relieves open channel block of Na + channels, generating a resurgent Na + current in the interspike interval that triggers the next action potential ( Raman and Bean, 1997 ; Khaliq et al, 2003 ; Grieco et al, 2005 ).…”
Section: Introductionmentioning
confidence: 99%